EVALUASI KEBIJAKAN MORATORIUM PADA PERKEBUNAN KELAPA SAWIT - Christiawan, Rio (Veritas et Justitia, 2020)
In 2018, the Indonesian government issued Presidential Instruction No. 8 of 2018 re. suspension and evaluation of palm oil plantation permits and boosting of its productivity (Moratorium policy).  This article is written as a critique, using a legal-dogmatic approach, directed towards this policy. It is noted that there exists uncertainty about which license, from the web of existing and relevant permits-licenses, are going to be suspended and evaluated. This legal uncertainty in the final analysis hampers the effort to make Indonesia prosperous as aspired by the 1945 Constitution (Art. 33).